Assessing Pedagogical Competence of Arabic Teachers: A Case Study of SDIT Permata Mulia Mojokerto - Saputra, Prayoga Ade; Ammar, Farikh Marzuki (Indonesian Journal of Islamic Studies, 2023)
This quantitative-qualitative research study aimed to assess the pedagogical competence of Arabic teachers at SDIT Permata Mulia Mojokerto based on the standards outlined in the Regulation of the Minister of National Education Number 16 of 2007. The research employed a descriptive quantitative analysis to interpret the data obtained through questionnaires and observations. The results revealed that the pedagogical competence of Arabic teachers at SDIT Permata Mulia Mojokerto was categorized as "Good" with a score of 3.33 (83.33%). The research findings indicate that the implementation of pedagogical competence was effective, although some areas such as language quality and Arabic language skills still require further attention. The implications of this study highlight the importance of ongoing professional development for Arabic teachers to enhance their language proficiency and instructional abilities, ultimately contributing to the improvement of Arabic language education in similar contexts.Highlight: Pedagogical competence assessment: This study examines the pedagogical competence of Arabic teachers at Permata Mulia Integrated Islamic Elementary School Mojokerto, focusing on various aspects of teaching and learning activities. Mixed-method approach: The research utilizes a combination of quantitative and qualitative methods, employing questionnaires and observations to collect data and descriptive quantitative analysis to interpret and describe the findings. Findings and implications: The study concludes that the implementation of pedagogical competence among Arabic teachers is categorized as "Good," meeting the standards set by the Ministry of National Education. However, the study also identifies the need for improvement in language quality and Arabic language skills, emphasizing the importance of ongoing professional development for teacher Keyword: Pedagogical Competence, Arabic Teachers, Quantitative-Qualitative Research, Permata Mulia Integrated Islamic Elementary School, Mojokerto.